Characterisation of meta-autunite: Towards identifying potential alteration products of spent nuclear fuel. (December 2020) - Frankland, Victoria L.; Milodowski, Antoni E.; Read, David
Abstract: Laser-based spectroscopic techniques offer potential for characterising the alteration products of spent nuclear fuel in settings where the use of more traditional analytical methods is impracticable. Among these alteration products, uranyl phosphate phases have long attracted interest owing to their potential to form passivating surfaces on primary uranium phases inhibiting further uranium dissolution. Two strontium-rich meta-autunite ((Ca, Sr)(UO2 )2 (PO4 )2 ·2–8(H2 O)) samples from the Mount Spokane uranium deposit, Washington, USA were characterised by multiple laser wavelength Raman and time-resolved laser fluorescence spectroscopy. Well-defined Raman features were obtained, particularly at a laser wavelength of 785 nm, but partially hydrated meta-autunite phases could not be differentiated by Raman alone. However, subtle differences in three key modes were observed between meta-autunite and published data for fully hydrated autunite specimens enabling these minerals to be distinguished. Seven luminescence emission and several excitation features were resolved for the two samples, with the latter being the first reported excitation data for meta-autunite. The luminescence decay lifetime was found to be significantly longer than previously reported and sensitive to the meta-autunite dehydration phase. Graphical abstract: Image 1 Highlights: Alteration of spent nuclear fuel in the presence of phosphate may result in meta-autunite formation. Type mineral specimens were characterised by SEM-EDXA, XRD, Raman and TRLFS. Fluorescence excitation spectrum for meta-autunite is reported for the first time. Fluorescence decay may be sensitive to meta-autunite dehydration. Raman features are sufficient to discriminate the phase from fully hydrated autunite.